Geoconservation: a new geosciences contribution for society - Brilha, J. B. (2011)
During the last two decades, geoconservation has been gradually entering into the geosciences’ community. In broad sense, geoconservation corresponds to the set of initiatives in order to identify, protect and manage the geological heritage, those exceptional occurrences of geodiversity with special importance for science, education, tourism, and culture. In many countries, geoconservation is still a marginal field of expertise, as nature conservation policies, either at an international scale or at a national one, usually forget the abiotic component of nature. Nevertheless, little by little geoconservation is gaining the deserved place within the Geosciences domain.